Retuning the catalytic bias and overpotential of a [NiFe]-Hydrogenase via a single amino acid exchange at the electron entry/exit site - Adamson,H; Robinson,M; Wright,JJ; Flanagan,LA; Walton,J; Elton,D; Gavaghan,DJ; Bond,AM; Roessler,MM; Parkin,A (Journal of the American Chemical Society, 2017)
The redox chemistry of the electron entry/exit site in Escherichia coli hydrogenase-1 is shown to play a vital role in tuning biocatalysis. Inspired by nature, we generate a HyaA-R193L variant to disrupt a proposed Arg–His cation−π interaction in the secondary coordination sphere of the outermost, “distal”, iron–sulfur cluster. This rewires the enzyme, enhancing the relative rate of H2 production and the thermodynamic efficiency of H2 oxidation catalysis. On the basis of Fourier transformed alternating current voltammetry measurements, we relate these changes in catalysis to a shift in the distal [Fe4S4]2+/1+ redox potential, a previously experimentally inaccessible parameter. Thus, metalloenzyme chemistry is shown to be tuned by the second coordination sphere of an electron transfer site distant from the catalytic center.